Improved in vivo efficacy of anti-hypertensive biopeptides encapsulated in chitosan nanoparticles fabricated by ionotropic gelation on spontaneously hypertensive rats - Auwal, Shehu Muhammad; Zarei, Mohammad; Tan, Chin Ping; Basri, Mahiran; Saari, Nazamid (MDPI, 2017)
Recent biotechnological advances in the food industry have led to the enzymatic production of angiotensin I-converting enzyme (ACE)-inhibitory biopeptides with a strong blood pressure lowering effect from different food proteins. However, the safe oral administration of biopeptides is impeded by their enzymatic degradation due to gastrointestinal digestion. Consequently, nanoparticle (NP)-based delivery systems are used to overcome these gastrointestinal barriers to maintain the improved bioavailability and efficacy of the encapsulated biopeptides. In the present study, the ACE-inhibitory biopeptides were generated from stone fish (Actinopyga lecanora) protein using bromelain and stabilized by their encapsulation in chitosan (chit) nanoparticles (NPs). The nanoparticles were characterized for in vitro physicochemical properties and their antihypertensive effect was then evaluated on spontaneously hypertensive rats (SHRs). The results of a physicochemical characterization showed a small particle size of 162.70 nm, a polydispersity index (pdi) value of 0.28, a zeta potential of 48.78 mV, a high encapsulation efficiency of 75.36%, a high melting temperature of 146.78 °C and an in vitro sustained release of the biopeptides. The results of the in vivo efficacy indicated a dose-dependent blood pressure lowering effect of the biopeptide-loaded nanoparticles that was significantly higher (p < 0.05) compared with the un-encapsulated biopeptides. Moreover, the results of a morphological examination using transmission electron microscopy (TEM) demonstrated the nanoparticles as homogenous and spherical. Thus, the ACE-inhibitory biopeptides stabilized by chitosan nanoparticles can effectively reduce blood pressure for an extended period of time in hypertensive individuals.